The Dynamics of Money Supply, Exchange Rate and Inflation in Nigeria (1986-2004) - Alfred, Ayodele Samuel (2015)
The study examined the exchange rate policies and monetary policies in Nigeria over the period of study 1986 – 2004, analysed the trend and pattern of exchange rate, money supply and inflation, investigated the long run relationship between monetary growth, exchange rate and inflation in Nigeria, and also determined the relative contribution of money supply and exchange rate on inflation. This was with a view to determining the relationship between money supply, exchange rate and inflation in Nigeria.